Squatting in the “era of permanent crisis” - Zheleznyak, Olga (project baikal, 2023)
The phenomenon of squatting, which plays an important role in the life of the city in the “era of permanent crisis”, is a kind of response to the crisis and/or an attempt to implement utopia, introduction of a special community model or reflection of the ideas of living ideals, as well as a form and method of creative self-expression and self-organization. It is a dual phenomenon, which is also a space of danger, risk and opportunities for self-development / self-realization.
Keywords: permanent crisis; squat; squatters; ghost cities; city